Harnessing potential of legumes for sustainable intensification of Indian agriculture - Dinesh Chand Meena; Kiran Kumara TM; Anjani Kumar (Agricultural Economics Research Review, 2024)
The inclusion of legumes in the cropping systems is recognized as a pathway for sustainable agricultural production with substantial environmental benefits. The legumes provide multiple ecosystem services to societies and agroecosystems, such as providing food, supplying nitrogen to crops through biological nitrogen fixation, reducing greenhouse gas emissions, improving carbon sequestration and soil fertility, and reducing water use and disease and pest infection. Despite these enormous benefits, the adoption level of legume crops is not very inspiring at the field level. The paper has highlighted the potential of legume-based cropping systems through a meta-analysis, using 555 pair observations from 134 studies, in generating additional ecosystem services in terms of physical quantity and monetary terms. Further, the study has identified reasons for the low adoption of legume crops and has provided some policy suggestions to improve the cultivated area under legumes.